2020
DOI: 10.3390/cancers12020485
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling Uncovers an Autoimmune Response Signature That Reflects Ovarian Cancer Pathogenesis

Abstract: Harnessing the immune response to tumor antigens in the form of autoantibodies, which occurs early during tumor development, has relevance to the detection of cancer at early stages. We conducted an initial screen of antigens associated with an autoantibody response in serous ovarian cancer using recombinant protein arrays. The top 25 recombinants that exhibited increased reactivity with cases compared to controls revealed TP53 and MYC, which are ovarian cancer driver genes, as major network nodes. A mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…In a screening involving 20 ovarian cancer patients and 17 controls, circulating auto-antibodies towards P53 and MYC were primarily found, followed by other proteins of the P53 and MYC networks both by a recombinant protein-based assay and by an immunoglobulin-bound protein assay [ 103 ]. A study reported by Yang et al [ 104 ] also focused on P53 auto-antibodies.…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…In a screening involving 20 ovarian cancer patients and 17 controls, circulating auto-antibodies towards P53 and MYC were primarily found, followed by other proteins of the P53 and MYC networks both by a recombinant protein-based assay and by an immunoglobulin-bound protein assay [ 103 ]. A study reported by Yang et al [ 104 ] also focused on P53 auto-antibodies.…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…Yang et al showed that in advanced EOC patients, p53-AAbs levels can be elevated 8 months prior to CA125 and 22 months prior to clinical diagnosis in patients who do not experience a rise in CA125, emphasizing the importance of p53 as a marker that could complement CA125 at the time of diagnosis [ 176 ]. Three other studies showed a potential for p53 AAbs for early EOC diagnosis [ 185 , 186 , 187 ]. However, data from a study involving 194 women with OC that aimed to estimate the diagnostic capacity of p53 AAbs for invasive EOC, indicated that the added value of p53-AAbs as a marker for early detection of OC is still limited [ 188 ].…”
Section: The Role Of P53 In Hgsc Microenvironmentmentioning
confidence: 99%
“…There is currently substantial interest in liquid biopsy approaches for cancer screening whether in a general population setting or for subjects at increased risk. A wide range of blood-based biomarkers are currently being investigated including circulating tumor DNA (ctDNA) representing mutations or altered methylation patterns; RNA, proteins, metabolites, autoantibodies to tumor antigens; exosomes; and circulating tumor cells [15][16][17][18][19][20] . Performance requirements depend on subjects' risk, with a need for very high specificity for subjects at average risk.…”
Section: Introductionmentioning
confidence: 99%